Social media, protest cultures and political subjectivities of the Arab spring. (January 2014) - Markham, Tim
This article draws on phenomenological perspectives to present a case against resisting the objectification of cultures of protest and dissent. The generative, self-organizing properties of protest cultures, especially as mobilized through social media, are frequently argued to elude both authoritarian political structures and academic discourse, leading to new political subjectivities or 'imaginaries'. Stemming from a normative commitment not to over-determine such nascent subjectivities, this view has taken on a heightened resonance in relation to the recent popular uprisings in the Middle East and North Africa. The article argues that this view is based on an invalid assumption that authentic political subjectivities and cultures naturally emerge from an absence of constraint, whether political, journalistic or academic. The valorization of amorphousness in protest cultures and social media enables affective and political projection, but overlooks politics in its institutional, professional and procedural forms.